Evaluation of The Digital Game Designed for Science Education by Academics, Teachers and Candidate Teachers - Varlık, Melike; Akgül, Güldem Dönel; Pınar, Mehmet Ali (Fırat University, 2025)
This study aimed to evaluate the effectiveness of educational digital games designed for biology teaching. Conducted at Erzincan Binali Yıldırım University, the research involved 5 computer education specialists, 5 science educators, 10 science teachers, and 40 prospective teachers, utilizing the relational survey model. The maximum diversity sampling method, one of the purposeful sampling methods, was adopted in the study. The designed digital educational biology material was presented to the participants, followed by applying a web-based educational material evaluation scale to all participants. The participants' opinions about the material were gathered through questions integrated into a section of the scale. The data collected were analyzed using SPSS software and the participants' opinions about the material were examined using descriptive analysis technique. As a result of the research, it was determined that all participants agreed that the designed digital educational biology material would support permanent learning by providing an interesting, motivating and entertaining environment for the lesson. It is anticipated that the material will facilitate meaningful learning by engaging sensory organs, simplifying the understanding of complex subjects, and increasing students' interest. However, academics, teachers, and pre-service teachers identified the shortcomings of the material. In particular, it was emphasized that not giving feedback according to students' answers was a major deficiency. In addition, it was emphasized that more sound effects, questions, activities, and animations should be added to the material, and increasing the duration of the game would enable students to learn the desired subject by having fun without getting bored. As a result of this study, it was seen that the aspects of the designed material need to be improved as well as the aspects that are liked.

Bu çalışma, biyoloji öğretimine yönelik bir dijital eğitsel oyunun etkisini değerlendirmeyi amaçlamaktadır. Scratch platformu kullanılarak geliştirilen oyun, biyoloji konularını eğlenceli ve anlamlı bir öğrenme ortamında sunmayı hedeflemiştir. Scratch, grafik, ses ve video gibi özellikleri destekleyen bir platform olarak öğrencilerin yaratıcı düşünme, problem çözme ve mantıksal akıl yürütme becerilerini geliştirmeye katkı sağlar. Araştırma, Erzincan Binali Yıldırım Üniversitesi'nde 5 bilgisayar eğitimi uzmanı, 5 fen eğitimcisi, 10 fen bilgisi öğretmeni ve 40 öğretmen adayıyla yürütülmüş ve ilişkisel tarama modeli kullanılarak gerçekleştirilmiştir. Katılımcılara dijital materyal sunulmuş, ardından web tabanlı eğitim materyali değerlendirme ölçeği uygulanmıştır. Katılımcıların materyal hakkındaki görüşleri, ölçeğin bir bölümüne yerleştirilen sorularla alınmıştır. Elde edilen veriler, SPSS programı kullanılarak analiz edilmiş ve katılımcıların materyal hakkındaki görüşleri betimsel analiz tekniği kullanılarak incelenmiştir. Ölçeklerden elde edilen sonuçlara göre, materyal öğretmen ve öğretmen adayları tarafından “çok iyi”, akademisyenler tarafından “iyi” olarak değerlendirilmiştir. Betimsel analiz sonuçları, materyalin anlamlı öğrenmeyi desteklediğini, karmaşık biyoloji konularını kolayca anlaşılabilir hale getirdiğini ve motivasyonu artırdığını ortaya koymuştur. Ancak geri dönüt mekanizmasının eksikliği ile daha fazla ses efekti ve animasyon eklenmesi gerektiği vurgulanmıştır. Materyal genel olarak biyoloji öğretiminde etkili bir öğrenme aracı olarak değerlendirilmiştir.
Biyoloji Öğretiminde Kullanılmak Üzere Geliştirilen Dijital Oyunun Akademisyen, Öğretmen ve Aday Öğretmen Görüşleriyle Değerlendirmesi
Keywords: Applied and Developmental Psychology (Other); Uygulamalı ve Gelişimsel Psikoloji (Diğer)